2014
DOI: 10.1155/2014/165897
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs in the Neural Retina

Abstract: The health and function of the visual system rely on a collaborative interaction between diverse classes of molecular regulators. One of these classes consists of transcription factors, which are known to bind to DNA and control the transcription activities of their target genes. For a long time, it was thought that the transcription factors were the only regulators of gene expression. More recently, however, a novel class of regulators emerged. This class consists of a large number of small noncoding endogeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
53
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(53 citation statements)
references
References 114 publications
0
53
0
Order By: Relevance
“…2012; Maiorano & Hindges 2012). miRNAs also play a key role in the regulation of polarization of microglial cells and have thus an effect on the progress of retinal disorders (Andreeva & Cooper 2014). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2012; Maiorano & Hindges 2012). miRNAs also play a key role in the regulation of polarization of microglial cells and have thus an effect on the progress of retinal disorders (Andreeva & Cooper 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated the essential roles of miRNAs in the development, survival and normal function of the retina (Almasieh et al 2012;Maiorano & Hindges 2012). miRNAs also play a key role in the regulation of polarization of microglial cells and have thus an effect on the progress of retinal disorders (Andreeva & Cooper 2014).…”
Section: Introductionmentioning
confidence: 99%
“…There are some microRNAs have relationship with DR, such as Mortuza et al (2014) explored the potential role of miR-195 in DR caused by hyperglycaemia changes. Further studies have also identified that miRs actively participate in retinal progression, homoeostasis and pathobiology, and miR-133b has been reported to show specific expression in retinal dopaminergic amacrine cells (Andreeva & Cooper 2014). Further studies have also identified that miRs actively participate in retinal progression, homoeostasis and pathobiology, and miR-133b has been reported to show specific expression in retinal dopaminergic amacrine cells (Andreeva & Cooper 2014).…”
Section: Introductionmentioning
confidence: 97%
“…are related to DR(Andreeva & Cooper, 2014). On the other hand, miRNA-126, miRNA-200b, and miRNA-31 are involved in vasculature regulation and therefore are crucial for suppression in DR.…”
mentioning
confidence: 99%